2017
DOI: 10.1016/j.carbon.2016.12.065
|View full text |Cite
|
Sign up to set email alerts
|

Systematic evaluation of different types of graphene oxide in respect to variations in their in-plane modulus

Abstract: Graphene oxide samples prepared in various laboratories following a diversity of synthesis protocols based on Brodie's (BGO) and Hummers/Offeman's (HGO) methods were compared in respect of their inplane moduli. A simple wrinkling method allowed for a spatial resolution <1.5 mm by converting the wrinkling frequency. Quite surprisingly, a drastic variation of the in-plane moduli was found spanning the range from 600 GPa for the best BGO types, which is in the region of chemically derived graphene, all the way do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
45
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 47 publications
(46 citation statements)
references
References 37 publications
1
45
0
Order By: Relevance
“…Harsh reaction conditions usually lead to materials with different physical properties and a distorted carbon lattice due to over‐oxidation . However, we demonstrated that by controlling the temperature of the reaction the carbon framework could be preserved .…”
Section: Figurementioning
confidence: 80%
“…Harsh reaction conditions usually lead to materials with different physical properties and a distorted carbon lattice due to over‐oxidation . However, we demonstrated that by controlling the temperature of the reaction the carbon framework could be preserved .…”
Section: Figurementioning
confidence: 80%
“…[49] Smaller number of defects in Brodie GO relative to Hummers GO is also supported by superior mechanical properties measured on individual Brodie graphene oxide flakes and multilayered membranes. [33] However, one needs to note that the effect of different impurities (first of all sulphur in HGO) on swelling properties of graphite oxides is not yet completely clear.…”
Section: Resultsmentioning
confidence: 99%
“…It should be noted here structural models of GO were proposed over past 20 years were mostly proposed based on studies of materials produced by Hummers oxidation, e.g. [9,14] However, BGO and HGO are different materials in respect to some key properties which include e.g swelling [29][30], exfoliation [30][31][32] and mechanical properties [33]. The difference between solvation/hydration properties of BGO and HGO was subject of several recent studies but remains to be poorly understood.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the dependence of the physicochemical properties of GO on the synthesis method has been highlighted and considerable sample‐to‐sample variations were also demonstrated . However, all sorts of graphene oxides are hydrophilic materials.…”
Section: Introductionmentioning
confidence: 99%